Time Sequence Map for Interpreting the Thermal Runaway Mechanism of Lithium-Ion Batteries With LiNixCoyMnzO2 Cathode - Feng, Xuning; Zheng, Siqi; He, Xiangming; Wang, Li; Wang, Yu; Ren, Dongsheng; Ouyang, Minggao (Frontiers in Energy Research, 2018)
Thermal runaway is one of the key failure reasons for the lithium-ion batteries. The potential of thermal runaway in applications increases when the industry starts to use high energy LiNixCoyMnzO2 cathode. The thermal runaway mechanism is still unclear, because the side reactions are complex. Heat generation during thermal runaway can be caused by the decomposition of individual cell components, or by interactive reactions between multiple components. This paper tries to comb the heat sources during thermal runaway using a novel method named the “Time Sequence Map” (TSM). The TSM tracks the heat sources according to the notion of thermodynamic systems. The thermodynamic system means a combination of materials that stay and react together, and generate heat independently without interruptions from other thermodynamic systems. With the help of the defined thermodynamic systems, researchers will be rescued from being trapped in the complex reactions, and the heat sources during thermal runaway can be clearly explained from bottom up. The thermal runaway results for two battery samples demonstrate the validity of the TSM. The TSM shows the heat sources including that: 1) fire, 2) internal short circuit, 3) oxidation-reduction reaction between the cathode and anode, etc. The contributions for the heat sources to the thermal runaway are further discussed. Conclusions come to: 1) the major heat source is the oxidation-reduction reaction; 2) the fire releases lots of heat, but most of the heat is not to heat the cell itself; 3) the internal short circuit is critical to trigger the oxidation-reduction reaction; 4) the internal short circuit is not the major heat source that heat the cell to 800℃ or higher; 5) the oxidation-reduction reaction is triggered when the temperature reaches a critical temperature. The TSM helps depict the frontiers in the researches of battery thermal runaway. It suggests that we focus on: 1) the relationship between internal short circuit and thermal runaway; 2) the mechanism of the oxidation-reduction reaction between the cathode and anode; 3) the detailed reaction mechanisms for a specific thermodynamic system within the cell.